Identifying languages in a novel dataset: ASMR-whispered speech - Song, Meishu; Yang, Zijiang; Parada-Cabaleiro, Emilia; Jing, Xin; Yamamoto, Yoshiharu; Schuller, Björn (Frontiers in Neuroscience, 2023)
The Autonomous Sensory Meridian Response (ASMR) is a combination of sensory phenomena involving electrostatic- like tingling sensations, which emerge in response to certain stimuli. Despite the overwhelming popularity of ASMR in the social media, no open source databases on ASMR related stim- uli are yet available, which makes this phenomenon mostly inaccessible to the research community; thus, almost com- pletely unexplored. In this regard, we present the ASMR- Whispered-Speech (ASMR-WS) database, a novel database on whispered speech, specifically tailored to promote the de- velopment of ASMR-like unvoiced Language Identification (unvoiced-LID) systems. The ASMR-WS database encom- passes 38 videos—for a total duration of 10 hours and 36 minutes—and includes seven target languages (Chinese, En- glish, French, Italian, Japanese, Korean, and Spanish).